(untitled) (International Association of Biologicals and Computational Digest, 2022)
The Methanolic extract of the Leaves of Moringa concanensis (family:Moringaceae) was tested for Phytochemicals and total flavonoid test. Qualitative phytochemical analysis of Moringa concanens is leaves extract was carried out with a view of developing leads for new therapeutic products. The results indicate that Moringa concanensis is rich in phytoconstituents. It also shows high amount of Flavonoid in Monsoon season as compared to summer which is important for human health because of their antioxidant, antimicrobial and anti-inflammatory activities.